AN OVERVIEW OF PSYCHOLOGICAL WELL-BEING ON WOMEN SURVIVORS OF DOMESTIC VIOLENCE - Hapsari, Elisabet Widyaning (Universitas Mercu Buana Jakarta, 2024)
Domestic violence (DV) has a negative impact on women, especially older adults who have endured it for the longest periods compared to other age groups. After separation, they need psychological well-being (PWB), which first requires going through a period of Post-Traumatic Growth (PTG). This involves positive coping after trauma, including greater appreciation for life, personal strength, spiritual change, closer relationships, and new possibilities (Tedeschi & Calhoun, 2012). Following PTG, these factors are adapted and directed toward good PWB, defined as the ability to accept oneself, maintain positive relationships, live independently, control one’s environment, have clear life goals, and strive for growth (Ryff, 1995). This study aims to describe the PWB of women survivors of domestic violence. Using a qualitative phenomenological approach, data were collected through in-depth interviews with three older adult informants. The findings show that all three informants underwent PTG: they adopted a growth mindset to develop themselves, sought help from others, recognized the importance of social support, deepened spirituality, and strengthened their relationship with God. These aspects contributed to excellent PWB, as all informants were able to accept themselves and forgive the past; maintain positive relationships with family, friends, and children; live autonomously; master their environment; achieve life goals and satisfaction; and strive for betterment for themselves, God, and others. Protective and risk factors also influenced their PWB